Stress-Induced Executive Dysfunction in GDNF-Deficient Mice, A Mouse Model of Parkinsonism - Buhusi, Mona; Olsen, Kaitlin; Yang, Benjamin Z.; Buhusi, Catalin V. (Frontiers in Behavioral Neuroscience, 2016)
Maladaptive reactivity to stress is linked to improper decision making, impulsivity, and discounting of delayed rewards. Chronic unpredictable stress (CUS) alters dopaminergic function, re-shapes dopaminergic circuits in key areas involved in decision making, and impairs prefrontal-cortex dependent response inhibition and working memory. Glial-derived neurotrophic factor (GDNF) is essential for regulating dopamine (DA) release in the basal ganglia and for the survival of dopaminergic neurons; GDNF-deficient mice are considered an animal model for aging-related Parkinsonism. Recently, GDNF expression in the striatum has been linked to resilience to stress. Here we investigated the effects of CUS on decision making in GDNF-heterozygous (HET) mice and their wild-type littermate controls (WT). Before CUS no differences in temporal discounting (TD) were found between genotypes. However, following CUS GDNF HET mice, having a partial reduction of GDNF levels, showed increased impulsive choice indexed by a reduction in percent Larger-Later (LL) choices in the TD paradigm, and a reduction in area under the TD curve. Moreover, stressed GDNF HET mice, but not their WT controls, showed decreased neuronal activation (number of cFos positive neurons) in the orbitofrontal cortex (OFC), nucleus accumbens (NA) core, and NA shell, suggestive of a maladaptive response to stress. Interestingly, area under the TD curve positively correlated with cFos activation in the NA core, and NA shell, but not with orbitofrontal activity. These results provide further evidence of the differential involvement of the OFC, NA core, and NA shell in impulsive choice, and identify GDNF-deficient mice as a double-hit (gene × environment) model of stress-related executive dysfunction, particularly relevant to substance abuse and Parkinson’s disease (PD).